Elevated methylation of cyclin dependent kinase inhibitor 2B contributes to the risk of coronary heart disease in women - Chen, Xiaomin (Exp Ther Med, 2019)
Cyclin dependent kinase inhibitor 2B (CDKN2B) encodes a cyclin-dependent kinase inhibitor that may enhance the formation of atherosclerotic plaques. The aim of the present study was to investigate the contribution of CDKN2B promoter methylation on the risk of coronary heart disease (CHD). The present results indicated a significant association between increased CDKN2B methylation and the risk of CHD (adjusted P=0.043). A breakdown analysis according to sex demonstrated that CDKN2B methylation was significantly associated with the risk of CHD in women (adjusted P=0.010), but not in men. A further breakdown analysis by age indicated a significant association of CHD in the women >60 years (P=0.024). Luciferase reporter gene assay results indicated that the CDKN2B promoter fragment significantly enhanced luciferase activity (P<0.001). In addition, CDKN2B transcription was significantly enhanced following treatment with 5-aza-2′-deoxycytidine methylation inhibitor in human aortic endothelial cells (HAEC) and human primary coronary artery smooth muscle cells (HPCASMC; P<0.05 and P<0.01), but not in 293 cells. Notably, estrogen treatment reduced CDKN2B methylation of several CpGs and significantly increased CDKN2B gene expression levels in HAEC, HPCASMC and 293 cells (P<0.05 and P<0.01). Additionally, treatment of HAEC and HPCASMC with simvastatin and γ-carboxy-L-glutamic acid reduced CDKN2B promoter methylation and increased CDKN2B transcription concomitantly. The present study suggests that CDKN2B promoter methylation may be associated with sex dimorphism in the pathogenesis of CHD.